Finite element vibration analysis of cooling system - Chua, Dan Eik Tat. (2012)
There are two main objectives for this paper. The first objective is to investigate and identify the natural frequencies of a cooling system installed in a plane. The second objective is to examine the effects of the attachment of 4 isolators to the cooling system.